ENDOVASCULAR HEMOSTASIS IN UTERINE BLEEDING IN PATIENTS WITH UTERINE LEIOMYOMA - M. M. Damirov; L. S. Kokov; G. Y. Belozerov; E. Y. Trofimova; O. N. Oleynikova; G. P. Titova (Неотложная медицинская помощь)
We report results of treatment for 72 patients with uterine leiomyoma (LM) of various sizes and location, who had arrived with excessive uterine bleeding. All patients underwent urgent or urgently-delayed endovascular hemostasis by performing uterine arteries embolization (UAE). We analyzed clinical features of the disease after UAE in various sizes of tumors and studied immediate and long-term results of UAE in patients with LM.